Thyroid Hormone Plays an Important Role in Cardiac Function: From Bench to Bedside - Yamakawa, Hiroyuki; Kato, Tomoko S.; Noh, Jaeduk Yoshimura; Yuasa, Shinsuke; Kawamura, Akio; Fukuda, Keiichi; Aizawa, Yoshiyasu (Frontiers in Physiology, 2021)
Thyroid hormone (TH) is synthesized in the thyroid gland and circulates in the blood stream to regulate all cells, tissues, and organs in the body. In particular, this hormone exerts several effects on the cardiovascular system. TH is known to increase the heart rate and cardiac contractility, alter the systolic and diastolic function of the heart, and decrease the systemic vascular resistance. In the past 30 years, several research groups have studied the molecular pathways that mediate the role of TH on the cardiovascular system, to better understand its mechanisms of action. The intracellular cardiac effects of TH occur via two mechanisms, genomic or non-genomic, with a genomic pathway playing the major role. In this review, we summarized the current knowledge on the TH action on the cardiovascular system, clinical and hemodynamic laboratory findings, and therapeutic management of patients with hyperthyroid or hypothyroid heart disease. Furthermore, we described the cardiovascular drugs that induce thyroid dysfunction and explained the mechanism of the thyroid toxicity of amiodarone, which is considered the most effective antiarrhythmic agent.